Biodegradation of phenol by Klebsiell aoxytoca selected from oil contaminated environments - Aamal Al-Saadi; Noor Mohammad Ali (Al-Qadisiyah Journal of Pure Science, 2020)
The degradation of phenol by microorganisms in the soil is an important method through which these materials are removed from the environment, thus reducing environmental pollution. Biodegradation by bacterial species provides unique opportunities to destroy or convert phenolic compounds into other less toxic compounds. In this study,  two Klebsiella oxytoca isolates were  selected from petroleum contaminated soils using mineral salts  medium supporting with phenol as the only carbon source.The isolates were identified by microscopic, morphological, and  biochemical approaches, and their capabilities of biodegrading phenol were analyzed by 4-aminoantipyrine assay. The results showed that the selected Klebsiella oxytoca isolates  were able to remove 100% of phenol even at a the highest used concentration(500 mg / L).The results of the current  study indicate the possibility of using Klebsiella oxytoca in bioremediation of phenol contaminated environments.